Developing an innovative materials enterprise in China: A nanotechnology small business case study. Issue 2 (19th August 2014) - Tang, Li; Shapira, Philip; Meng, Yu
Abstract : Purpose: This paper explores pathways and issues of small business technological commercialization in China, probing the particular characteristics of the Chinese context and the ways in which innovation frameworks, institutions and business strategies are embedded. Design/methodology/approach: We examine in detail the case of an innovative Chinese indigenous small firm engaged in innovative nanotechnology materials development. We investigate the strategies and push- and pull-factors underlying the company's innovation practices. We explore the proposition that the institutional relationships formed to secure access to research expertise and aid business survival also influence the ways in which technology is commercialized. Findings: We find that while technological development is company driven, it is also highly connected to regional innovation structures and networks. This stimulates a "spin-in" rather than a university-led model of development, as this small firm embeds its technology and business development strategies in conjunction with partner organizations. Broader management and policy implications are discussed. Originality/value: While China has rapidly expanded scientific research in emerging technologies such as nanotechnology, commercialization through the development of entrepreneurial technology-oriented small companies faces a series of challenges. New enterprises in the emerging area of nanotechnology encounter problems of technology transfer and intellectual property management, capital acquisition, market uncertainty, and constrained access to global markets.